Effects of enhanced bolus flavors on oropharyngeal swallow in patients treated for head and neck cancer. Issue 8 (21st August 2012) - Roa Pauloski, Barbara; Logemann, Jerilyn A.; Rademaker, Alfred W.; Lundy, Donna; Sullivan, Paula A.; Newman, Lisa A.; Lazarus, Cathy; Bacon, Mary
Abstract Background Treatment for head and neck cancer can reduce peripheral sensory input and impair oropharyngeal swallow. This study examined the effect of enhanced bolus flavor on liquid swallows in these patients. Methods Fifty‐one patients treated for head and neck cancer with chemoradiation or surgery and 64 healthy adult control subjects served as subjects. All were randomized to receive sour, sweet, or salty bolus flavor. Patients were evaluated at 7–10 days, 1 month, and 3 months after completion of tumor treatment. Control subjects received 1 assessment. Results All bolus flavors affected oropharyngeal swallow; sour flavor significantly shortened pharyngeal transit time across all evaluations. Conclusions Sour flavor influenced the swallow of patients treated for head and neck cancer, as well as that of control subjects in a manner similar to those with neurologic impairment observed in an earlier study. Sour flavor may improve the speed of pharyngeal transit regardless of whether a patient has suffered peripheral or central sensory damage. © 2012 Wiley Periodicals, Inc. Head Neck, 2013